The Implementation of E-Learning Web-based Model Centric Course (Edmodo) toward The Mathematics’ Interest and Learning Outcomes - Yustinaningrum, Bettri (Al-Jabar: Jurnal Pendidikan Matematika, 2018)
The aim of this research is to know the effect of application of E-Learning model based on Web-Centric Course with Edmodo application media to increase: (1) the interesting of learning mathematics, (2) The mathematics student learning outcomes. The research method is used in quantitative research with the quasi-type experimental design, as well as research design using the pre-test and post-test control group. The Instrument has used the test of mathematics learning outcomes and questionnaire interest in learning mathematics students. The data hypothesis test uses the t-test involving pre-requisite tests (normality and homogeneity) beforehand. The result of this research is the application of E-Learning model based on Web-Centric Course with Edmodo application media has an effect on: (1) the student learning outcomes of mathematics; (2) the interesting of learning mathematics students.